2005
DOI: 10.1021/ef049672r
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Weight Calibration of Asphaltenes Using Gel Permeation Chromatography/Mass Spectrometry

Abstract: Molecular weight (MW) is one of the most important properties of asphaltene. To determine the precise average MW using gel permeation chromatography (GPC), the MWs obtained for three different asphaltenes using GPC (MWps) and GPC-MSD (MWms) were compared. MWms proved independent of asphaltene type and had values similar to MWps for a MW of ∼900 but was significantly different in the lower-MW range, with a linear correlation between MWms and MWps. More-precise average MW values can be obtained using a revised c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0
4

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 17 publications
(32 reference statements)
2
53
0
4
Order By: Relevance
“…On the other hand, a significant number of LDI investigations have concluded that asphaltenes are considerably heavier, with MWD peaking at 1500–2000 amu or above, and extending to several thousand amu 27–29. These latter results are typically in agreement with measurements based on vapor pressure osmometry27, 34, 39 and gel permeation or size–exclusion chromatography 11, 29, 30…”
Section: Introductionsupporting
confidence: 71%
See 1 more Smart Citation
“…On the other hand, a significant number of LDI investigations have concluded that asphaltenes are considerably heavier, with MWD peaking at 1500–2000 amu or above, and extending to several thousand amu 27–29. These latter results are typically in agreement with measurements based on vapor pressure osmometry27, 34, 39 and gel permeation or size–exclusion chromatography 11, 29, 30…”
Section: Introductionsupporting
confidence: 71%
“…The complexity and heterogeneity of asphaltenes has become a defiant benchmark for analytical techniques. Therefore, this topic has motivated intense experimental efforts in the past years22–40 and, not surprisingly, it has also constituted a source of constructive controversy around the potentiality and limitations of the different experimental methods and the interpretation of the observations.…”
Section: Introductionmentioning
confidence: 99%
“…Size-exclusion chromatography (SEC) could also obtain a higher asphaltene molecular weight value than that from MS due to the association phenomenon. However, a more precise average MW can be obtained when using calibration curves on the basis of chemicals that better mimic the chemical functionalities of real petroleum fractions instead of conventional polymer standards [27,75,76]. Fluorescence decay and depolarization were once used to measure the molecular size and weight of asphaltenes by calibrating with known compounds [77,78].…”
Section: Sequential Elution Fractionation (Sef)mentioning
confidence: 99%
“…Size exclusion chromatography (SEC), also referred to as gel permeation chromatography (GPC), separates molecules according to their linear molecular size, based on their distribution between a stationary phase of controlled pore size distribution and a liquid mobile phase. 28 Hence, longer molecules elute faster than shorter molecules. The SEC chromatograms obtained define the change in UV signal against molecular size in relation to molar mass.…”
Section: Molar Mass Distribution Of the Productsmentioning
confidence: 99%